Antimicrobial and Cytotoxic Activities Screening of Marine Invertebrate-Derived Fungi Extract from West Sumatera, Indonesia - Bakhtra, Dwi; Yanwirasti, Yanwirasti; Wahyuni, Fatma Sri; Aminah, Ibtisamatul; Handayani, Dian (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The coral reef on Mandeh Island, West Sumatra, Indonesia, consists of an abundant source of sponge and soft coral. Secondary metabolites of marine-derived fungi isolated from the sponge and soft coral possess numerous biological activities. AIM: This study collected, identified, and screened marine-derived fungi isolated from marine invertebrates for antibacterial and cytotoxic bioactivities. MATERIALS AND METHODS: The marine invertebrates used are sponges; Xestospongia testudinaria and Placortis communis) and soft corals (Sarcophyton elegan and Subergorgia suberosa). The EtOAc extracts were analyzed for antimicrobial and cytotoxic activities using the diffusion agar method and brine shrimps lethality test. RESULTS: After cultivating on rice medium, the EtOAc extracts of 22 isolated fungi showed potent antimicrobial activity with an inhibitory zone of 15.9 mm against Staphylococcus aureus (XT2 extract), and Pseudomonas aeruginosa of 26.7 mm (XT6 extract), and Candida albicans of 29 mm (SE5 extract). XT6 extract showed the potential cytotoxic activity with an LC50 value of 100 μg/ml. CONCLUSION: The ability of the marine-derived fungi to produce bioactive compounds is promising potential as a source of antimicrobial and cytotoxic compounds.